2022
DOI: 10.1186/s13018-021-02746-2
|View full text |Cite
|
Sign up to set email alerts
|

Synovial calprotectin for the diagnosis of periprosthetic joint infection: a diagnostic meta-analysis

Abstract: Background Periprosthetic joint infections (PJI) are a rare but severe complication of total joint arthroplasty (TJA). However, the diagnosis of PJI remains difficult. It is one of the research that focuses about diagnosis for PJI for majority researchers to discover a novel biomarker. This meta-analysis tried to evaluate diagnostic value of synovial calprotectin for PJI. Methods This meta-analysis search of the literature was conducted in PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Even though there are few studies on the use of the synovial calprotectin level in the diagnosis of PJI, a meta-analysis found that this biomarker had a specificity of 84–99% and sensitivity of 84–98% in the diagnosis of PJI [ 73 ].In light of these data, it has been stated that the synovial calprotectin level can be used as a reliable biomarker in the diagnosis of PJI and it has been argued that it may be preferred owing to its low cost [ 74 ]. These promising developments have been supported by the findings of another recent meta-analysis and study [ 75 , 76 ]. It is obvious that the synovial calprotectin level, a promising agent in the diagnosis of PJI, will increasingly occupy a place in daily practice in the future.…”
Section: Biomarkers In Synovial Fluidmentioning
confidence: 72%
“…Even though there are few studies on the use of the synovial calprotectin level in the diagnosis of PJI, a meta-analysis found that this biomarker had a specificity of 84–99% and sensitivity of 84–98% in the diagnosis of PJI [ 73 ].In light of these data, it has been stated that the synovial calprotectin level can be used as a reliable biomarker in the diagnosis of PJI and it has been argued that it may be preferred owing to its low cost [ 74 ]. These promising developments have been supported by the findings of another recent meta-analysis and study [ 75 , 76 ]. It is obvious that the synovial calprotectin level, a promising agent in the diagnosis of PJI, will increasingly occupy a place in daily practice in the future.…”
Section: Biomarkers In Synovial Fluidmentioning
confidence: 72%
“…In a study by Warren et al, synovial calprotectin at a threshold of 50 mg/L was shown to have an AUC of 0.969, a sensitivity of 98.1%, and a specificity of 95.7% 89 . Furthermore, in a meta-analysis, Peng et al found that synovial calprotectin demonstrated a pooled AUC of 0.980, sensitivity of 94.0%, and specificity of 93.0% 90 . However, the literature on calprotectin remains limited, and additional studies with larger sample sizes are required to determine its diagnostic utility in the workup of PJI.…”
Section: Synovial Markersmentioning
confidence: 99%
“…While further research on calprotectin is necessary, according to recent diagnostic meta-analyses [ 117 , 118 ] synovial calprotectin has the potential to be a promising biomarker for diagnosing PJI due to its benefits, including its high diagnostic accuracy and convenience. However, it is important to note that current data are insufficient in order to be able to consider synovial calprotectin as a suitable stand-alone diagnostic marker for PJI.…”
Section: Diagnostic Testsmentioning
confidence: 99%